An easy method for quantification of anaerobic and microaerobic gene expression with fluorescent reporter proteins - Lucas Pedraz; Eduard Torrents (BioTechniques, 2023)
Fluorescent proteins, such as green fluorescent proteins, are invaluable tools for detecting and quantifying gene expression in high-throughput reporter gene assays. However, they introduce significant inaccuracies in studies involving microaerobiosis or anaerobiosis, as oxygen is required for the maturation of these proteins' chromophores. In this study, the authors highlight the errors incurred by using fluorescent proteins under limited oxygenation by comparing standard fluorescence-based reporter gene assays to quantitative real-time PCR data in the study of a complex oxygen-regulated gene network. Furthermore, a solution to perform quantification of anaerobic and microaerobic gene expression with fluorescent reporter proteins using a microplate reader with an oxygen control system and applying pulses of full oxygenation before fluorescence measurements is provided.